Breaking wild ebook - Les Becquets, Diane (2016)
When one woman goes missing in the Colorado wilderness, another becomes bent on discovering her whereabouts in this unforgettably moving, bestselling literary debut.   Driven to spend days alone in the wilderness, Amy Raye Latour, mother of two, is compelled by the quiet and the rush of nature. But this time, her venture into a remote area leaves her on the verge of the precarious edge that she’s flirted with her entire life.   When Amy Raye doesn’t return to camp, ranger Pru Hathaway and her dog respond to the missing person call. After an unexpected snowfall and few leads, the operation turns into a search and recovery.   As the novel follows Amy Raye and Pru in alternating threads, Breaking Wild assumes the white-knuckled pace of a thriller, laying bare Amy Raye’s ultimate reckoning with the secrets of her life and Pru’s dogged pursuit of the woman who, against all odds, she believes she can find.